Clinical researchShort period of exercise causes rapid increase of serum interleukin 6 with no effect on its soluble receptor - Kamiński, Karol; Jasiewicz, Małgorzata; Knapp, Małgorzata; Jackowska, Anna; Latocha-Korecka, Grażyna; Waszkiewicz, Ewa; Musiał, Włodzimierz J. (Archives of Medical Science, 2009)
Introduction: Interleukin 6 (IL-6) is a pleiotropic cytokine secreted by skeletal muscle during exercise, intermediating beneficial effects of physical training such as increasing insulin sensitivity and suppressing pro-inflammatory cytokines. As IL-6 actions depend on its soluble receptor (sIL-6R), the changes in IL-6 concentration should be analyzed together with the changes of the sIL-6R. Material and methods: We have performed a study to investigate the effects of short term exercise on plasma concentrations of IL-6 and sIL-6R in healthy subjects. Twenty four healthy, non-obese males (age 40-59) were included in the study. A 9 min standard Bruce protocol treadmill stress test was performed. Plasma IL-6 and sIL-6R concentrations were assessed prior to the exercise test and immediately after the 9th min of exercise. Results: Resting plasma IL-6 and sIL-6R concentrations were 1.54 ±0.43 pg/ml and 40 ±10.5 ng/ml respectively. After exercise IL-6 concentration increased to 2.08 ±0.89 pg/ml (p < 0.005 in comparison to baseline). The concentration of sIL-6R was similar to the initial values (39.6 ±7.4 ng/ml). In regression analysis the extent of IL-6 increase during exercise depended mainly on the maximal heart rate and systolic blood pressure. Analysis of ROC revealed that patients with lower maximal heart rate (< 140 bpm) and systolic blood pressure (< 160 mm Hg) were more likely not to have IL-6 rise after exercise. Conclusions: In healthy males, brief exercise causes significant increase of plasma IL-6 concentration that depends on hemodynamic effects of exercise, whereas the plasma concentration of IL-6 circulating receptor remains stable.